(untitled) - Rodman, George (New York, 2006)
Essentials of Management concisely surveys current management theories and research. Through a variety of real world examples from small, medium, and large companies the reader learns how those ideas are used by practicing managers. The organization of this text follows the mainstream functional approach of planning, organizing, leading, and controlling; but the content is flexible and encourages instructors to use the organization they are most comfortable with
Keywords: Mass media,Truyền thông đại chúng,Mass media,Truyền thông đại chúng,Mass media,Truyền thông đại chúng; History,Lịch sử,Social aspects,Khía cậnh xã hội